2019
DOI: 10.1177/0959683619854523
|View full text |Cite
|
Sign up to set email alerts
|

Long-term climate, vegetation and fire regime change in a managed municipal water supply area, British Columbia, Canada

Abstract: Post-glacial climate, vegetation and fire history were reconstructed from a sediment record from Begbie Lake, British Columbia, Canada, located in a municipal water supply area servicing > 350,000 people. Watershed managers have identified wildfire as a threat to water supply and seek to understand how vegetation and fire have varied through time with climate. In the cold late-glacial, open Pinus woodlands, periodically disturbed by fire, transitioned to mixed conifer forests subject to high-severity fire. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 80 publications
1
10
0
Order By: Relevance
“…At ~7300 cal yr BP, there is a notable increase in Q. garryana pollen at Roe Lake and by 6500 cal yr BP, Q. garryana accounts for 16% of the pollen assemblages (Figure 5). Nearby pollen records on Vancouver Island (e.g., Brown et al, 2022, 2019; Pellatt et al, 2001) show similar increases in Quercus , reflecting the establishment of Garry oak savanna communities throughout the region. At this time, fires continue to be frequent on Pender Island with fires occurring, on average, every 101 ± 29 years between 7300 and 6000 cal yr BP.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…At ~7300 cal yr BP, there is a notable increase in Q. garryana pollen at Roe Lake and by 6500 cal yr BP, Q. garryana accounts for 16% of the pollen assemblages (Figure 5). Nearby pollen records on Vancouver Island (e.g., Brown et al, 2022, 2019; Pellatt et al, 2001) show similar increases in Quercus , reflecting the establishment of Garry oak savanna communities throughout the region. At this time, fires continue to be frequent on Pender Island with fires occurring, on average, every 101 ± 29 years between 7300 and 6000 cal yr BP.…”
Section: Discussionmentioning
confidence: 95%
“…Previous work has shown that fire was uncommon throughout the region at the start of the Holocene, around 12,000 calendar years before present (cal yr BP), but increased over time as temperatures increased in the early Holocene (Walsh et al, 2015). By 10,000 cal yr BP, fire frequency was high at many sites in the Pacific Northwest (e.g., Brown et al, 2022Brown et al, , 2019Prichard et al, 2009;Walsh et al, 2015Walsh et al, , 2010Walsh et al, , 2008White et al, 2015). Warmer and drier climate in the early Holocene coupled with increased seasonality would have facilitated this period of more frequent fire.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to spatial variability in fire regimes, paleoecological reconstructions from charcoal, fossil pollen, and plant macrofossils in lake sediments, peat, and soil provided evidence of temporal instability throughout the Holocene (Senici et al 2013;Remy et al 2018) (Hallett et al 2003;Hoffman et al 2016;Brown et al 2017Brown et al , 2019, while fire declined during the Medieval Warm Period along the moisture-limited prairie-forest ecotone due to shifts in species composition to less fire-prone species (Campbell and Campbell 2000). Recent analyses have documented ecologically meaningful human influences on fire regimes over centuries to millennia (Blarquez et al 2018;Hoffman et al 2016Hoffman et al , 2017Murphy et al 2019).…”
Section: Fire Regime Characterizationmentioning
confidence: 99%
“…Due to the coarse resolution of the age-depth model, the record of North Slave Region fire events only extends back to the late nineteenth century (Pelletier et al, 2020). Previous studies have employed multiple proxies derived from lake sediments to successfully reconstruct Holocene paleofire records and vegetative histories (Brown et al, 2019;Gaboriau et al (2020).…”
Section: Discussionmentioning
confidence: 99%